2013
DOI: 10.1016/j.jvir.2013.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Tunneled Dialysis Catheters Placed for Hemodialysis Initiation

Abstract: PURPOSE Over 80% of US patients initiate HD with a tunneled dialysis catheter (TDC). Published data on TDC outcomes are based on a case-mix of prevalent and incident TDCs. We analyzed factors affecting patency and complications of first TDCs ever placed in a large cohort of incident HD patients. MATERIALS AND METHODS We retrospectively queried a prospective, computerized vascular access database to identify 472 patients receiving a first ever TDC. Multiple variable survival analysis was used to identify clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
85
4
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 25 publications
(28 reference statements)
4
85
4
3
Order By: Relevance
“…Raheem et al reported a 90‐day catheter survival rate of 77% . Similarly, Shingarev et al reported a 3‐month catheter patency rate of 69% . Catheter survival in our patients was slightly lower than those reports.…”
Section: Discussioncontrasting
confidence: 47%
“…Raheem et al reported a 90‐day catheter survival rate of 77% . Similarly, Shingarev et al reported a 3‐month catheter patency rate of 69% . Catheter survival in our patients was slightly lower than those reports.…”
Section: Discussioncontrasting
confidence: 47%
“…About tCVC survival rate, Shingarev et al [18] reported that the first tCVC survival rate was 34% during the first year. The tCVC failure due to catheter-related infections was 45%.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous haemodialysis catheters serve as an important temporary vascular access during maturation of other permanent AV accesses, such as fistulae or grafts, or PD catheter is not ready for use . However, the NKF KDOQI guidelines suggest that prevalent long‐term or permanent CVC rates of less than 10% may be a realistic target . Therefore, avoiding insertion of CVC or removal of unnecessary CVC in order to minimize the related complications is the most important statergy …”
Section: Care Of Patient For Insertion Of Percutaneous Catheter Fomentioning
confidence: 99%